PENILAIAN USER EXPERIENCE APLIKASI JAHIT BATIK ASYIK (JATIK ASYIK) OLEH GURU SEBAGAI MEDIA PEMBELAJARAN DI SEKOLAH MENENGAH KEJURUAN - Miftahur Rizkiah, - (2021)
User Experience is an important design construction used for current technology acceptance, be it websites, smartphone applications, software or other digital products where UX greatly affects user satisfaction (Amalina and Helni Mutiarsih Jumhur 2018) (Tremblay et al. 2020). This study discusses "User Experience Assessment of the Fun Batik Sewing Application (Jatik Asyik) for Vocational High School Teachers". focused on the aspects of usability and user experience which is an umbrella research. The research design used is a qualitative exploratory study with the main activities being interviews, focus group discussions and questionnaires related to user experience dimension data. The results of the study stated that the learning media used by the teacher were still conventional. The electronic media used was limited to the use of power points. The Jatik Asyik application is considered easy to use and recommended for use as a learning medium. The assessment is based on user experience based on the recap of respondents' highest assessment on the strategy plane, the percentage is 90% with agreed criteria, 90% scope plane with agreed criteria, 80% plane structure with agreed criteria, 50% skeleton plane with agreed criteria, 50% surface plane with criteria doubtful